Exploring the adoption of self-service checkouts and the associated social obligations of shopping practices. (May 2018) - Bulmer, Sandy; Elms, Jonathan; Moore, Simon
Abstract: While retailers and other service providers are increasingly introducing self-service checkouts into stores, these technologies do not have universal appeal for consumers. The literature offers limited understanding of how self-service checkouts influence shopping practices and consumers' experiences of the in-store environment. Using the lens of practice theory, this paper explores adoption of self-service checkouts by consumers. Semi-structured face to face interviews were used to capture consumers' discursive accounts of their shopping practices, and to examine their interactions with self-service checkouts. Findings illustrate that unwilling customers feel a sense of social obligation to use self-service checkouts at times in order to help others. This study provides a broader appreciation of how consumers engage with self-service checkout processes, and extends understanding of how consumers manage the paradoxes that surround the introduction of in-store technologies by retailers. The managerial implications of self-service checkouts for retailers are also discussed.